The Meaning of Malay Proverbs Based on Inquisitive Semantics and the Preparation of Lesson Plans Using the Copying Assignment Technique - Kasrizal; Wulandari, Utari; Hermandra (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) Malay proverbs that use the word air based on inquisitive semantics; 2) the lesson plan for learning the meaning of Malay proverbs that use the word air based on inquisitive semantics through copying assignments in special teaching materials. This literature research was conducted in the fall semester of 2024/2025. The objects of this study were ten Malay proverbs that use the word air. To collect data on the meaning of Malay proverbs based on inquisitive semantics that use the word air, observation guidelines, and questionnaires were arranged objectively and systematically. Data on the meaning of Malay proverbs that use the word aur were analyzed using a thematic approach based on inquisitive semantics. Data on the implementation plan for learning were analyzed thematically based on the technique of copying assignments and test techniques in special teaching materials. The results of the study: 1) there is a description of the meaning of ten Malay proverbs that use the word air based on inquisitive semantics; 2) the implementation plan for learning the meaning of Malay proverbs that use the word water based on inquisitive semantics through the technique of copying assignment and test techniques in special teaching materials for grade X senior high school students containing 5 initial activities, 31 core activities, and 2 final activities.